A study on the Barangay Loyola Heights Community's perception of the sustainainability of the Barangay Loyola Heights Community-based Toy Library - Victorio, Mico Paulo M. (School of Library and Information Studies, University of the Philippines Diliman, 2012)
This study focused to determine the perception of the Barangay Loyola Heights Community towards the role of the toy library in consideration of its sustainability by identifying the strengths, weaknesses, opportunities, and threats; to know their views on sustainability and ways of approaching it; to identify ways in which the community can support and contribute to the toy library's sustainability, and; to determine the practices and strategies that the toy library must do to improve its programs and services.